Investigating drill constraint kinematics in male baseball pitchers using markerless motion capture - Dobos, T. J.; Bench, R. W.; Richards, L.; Mckinnon, C.; Holmes, M.; Sonne, M. (ISBS Proceedings Archive (Michigan), 2023)
This study investigated the kinematic differences that pitching constraint drills elicit compared to a baseball pitch. 18 male baseball pitchers with average height (183.7 ± 5.2cm), weight (87.4 ± 9.6kg), and skill level (Professional (4), Collegiate (5), High School (9)) were included. Video was recorded using a single camera from the open side. Each pitcher threw 3 maximum effort pitches from a mound. Next, 3 maximum effort throws were recorded for 8 different throwing drills: medicine ball hook`em drill, pivot pickoff drill, foot-up rocker drill, walk-in drill, towel drill, janitor drill, drop-step drill, and long toss. Videos were processed using pitchAITM, a markerless motion capture solution. The medicine ball hook`em drill was the most different to a pitch, and the towel drill was the most similar. This work demonstrates the first collective approach to studying the biomechanics of frequently used baseball pitching constraint drills.